New morphological data on Colobomatus belizensis Cressey and Schotte, 1983 (Copepoda: Philichthyidae), parasitic in the mandibular canals of the white grunt, Haemulon plumierii (Lacepède, 1801) (Actinopterygii: Haemulidae) off Rio de Janeiro, southeastern Brazil - Jonatha Lopes; João Victor Couto; Felipe Bisaggio Pereira; Fabiano Paschoal (Nauplius)
ABSTRACT New morphological and morphometric data on females of Colobomatus belizensis Cressey and Schotte, 1983 is provided based on specimens collected from the mandibular canals of Haemulon plumierii (Lacepède) in Sepetiba Bay, state of Rio de Janeiro, southeastern Brazil. Specimens were identified as C. belizensis by the presence of a smooth, not bifid, anterior cephalic process, two pairs of dorsolateral thoracic processes with rounded tips, and third abdominal somite with one pair of lateral process with rounded tips. The original description of the female of C. belizensis was superficial, lacking details on some structures with taxonomic value that are fully described here, such as the processes ornamented with six sensilla, caudal rami armed with 11 elements, as well as the armature of the legs and ornamentation of the buccal cone. These new data add robustness to the diagnosis and confirm the validity of C. belizensis, contributing to the taxonomy of the genus Colobomatus as a whole.